Science Materials with Guided Discovery Methods to Increase Problem Solving Ability for Junior High Schools - Hadiwiyono, Syamsul; Degeng, I Nyoman Sudana; Sitompul, Nurmida Catherine (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Science learning aims to improve problem-solving skills, and the guided discovery method has been proven to improve problem-solving skills. However, this method has not been widely practiced because teachers have difficulty designing this learning. This research aims to produce science learning materials using The Guided Discovery method for problem-solving learning for junior high school students on Light. The subjects of this study were VIII-grade students. Questionnaires and tests collected data. Questionnaires were used to obtain product feasibility, and tests were used to measure product effectiveness. Data analysis used percentages, paired t-tests, and one-way ANOVA. The results showed that, the development product meets the feasibility of being an effective learning material to build problem-solving skills. So, it can be said that products for science subjects using the Guided Discovery method are feasible and effective to be used as teaching materials to develop problem-solving skills for junior high school students, especially in the material of Light. The implication of this research shows that the product of science teaching materials based on the Guided Discovery method has the potential to be applied in the junior high school learning environment, especially in the topic of Light.